2016
DOI: 10.1242/dev.114231
|View full text |Cite|
|
Sign up to set email alerts
|

The many faces of hematopoietic stem cell heterogeneity

Abstract: Not all hematopoietic stem cells (HSCs) are alike. They differ in their physical characteristics such as cell cycle status and cell surface marker phenotype, they respond to different extrinsic signals, and they have different lineage outputs following transplantation. The growing body of evidence that supports heterogeneity within HSCs, which constitute the most robust cell fraction at the foundation of the adult hematopoietic system, is currently of great interest and raises questions as to why HSC subtypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 118 publications
(162 reference statements)
3
61
0
1
Order By: Relevance
“…We do not intend here to provide detailed overview of non-human models, as this extensive topic has been reviewed recently by us and by others Kim et al, 2014;Ciau-Uitz et al, 2016;Kauts et al, 2016;Robertson et al, 2016;Crisan and Dzierzak, 2016). Owing to the high accessibility of model organisms for experimentation and the genetic variability and rarity of human embryonic material, the analysis of human haematopoietic development has lagged behind these wellestablished experimental models and for a long time was limited to immunohistological and in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…We do not intend here to provide detailed overview of non-human models, as this extensive topic has been reviewed recently by us and by others Kim et al, 2014;Ciau-Uitz et al, 2016;Kauts et al, 2016;Robertson et al, 2016;Crisan and Dzierzak, 2016). Owing to the high accessibility of model organisms for experimentation and the genetic variability and rarity of human embryonic material, the analysis of human haematopoietic development has lagged behind these wellestablished experimental models and for a long time was limited to immunohistological and in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that contact between HSCs and stromal cells is important for maintaining HSC function [48,49]. The stromal cells from bone marrow include osteoblasts, macrophages, endothelial cells, and mesenchymal cells [50,51]. Mesenchymal cells are multipotent progenitor cells that can differentiate into mesenchymal cells, such as osteoblasts, adipocytes, and chondrocytes, and also have the potential for differentiation into cells such as neurons and lung cells [52].…”
Section: Stem Cell Culture Methodsmentioning
confidence: 99%
“…With the discovery of markers that can subdivide the niches, more exciting biology awaits. For example, HSCs are heterogenous in their cell cycle status, marker expression, lineage output and response to extrinsic signals . This raises the question as to whether there is heterogeneity within the niches.…”
Section: Perspectivesmentioning
confidence: 99%